Determination of Operating Conditions of a Probe Block Designed for Fault Diagnostics in Rail Heads - RANACHOWSKI, Zbigniew; MACKIEWICZ, Sławomir; KATZ, Tomasz; DĘBOWSKI, Tomasz; STARZYŃSKI, Grzegorz; LEWANDOWSKI, Marcin; ANTOLIK, Łukasz (Engineering Transactions, 2025)
In this paper, the key parameters influencing the proper operation of ultrasonic probes for railway rails diagnostics are determined. The goal is to test a set of ultrasonic probes under conditions occurring at high diagnostic speeds. Four issues are studied in more detail. The probe block-rail contact force required to obtain maximum echo level is determined. In the authors’ opinion, the key aspect is the design of the water irrigation nozzle shape in order to produce a laminar couplant flow under the probes. The dependence of the amplitude of the recorded echo on the coupling layer thickness is experimentally investigated. The population of registered signal samples is processed to determine the testing speed limit, which resulted from the loss of data validation ability. The speed limit is calculated based on the average value of the amplitude of the measured signal and the standard deviation of the registered population of amplitudes.The conducted research allows the authors to conclude that the instrumentation they developed enables the recording of an ultrasonic signal propagating through the tested rail at scanning speed of up to 100 km/h.